Analisis Kebutuhan E-Learning Untuk Pengembangan Mutu KBM Dengan Soft System Methodology Pada SMK di Semarang. - Hendri Rasminto; Fujiama Diapoldo Silalahi; Budi Hartono (STEKOM PRESS, 2020)
Analysis of E-Learning Information Systems is certainly one of the efforts that can be made to overcome problems that arise in the process of implementing teaching and learning activities (KBM) in each school. Soft System Methodology (SSM) analysis is a method used to help model unstructured problems. The SSM methodology is suitable for assisting an organization in defining their goals and then building a human activity system to achieve those goals. The relationship between the internal and external academic community involves teachers, parents of students, students and school administrators to develop information for supervision and student Development approaches. E-Learning analysis using the Soft Systems Methodology (SSM) approach is expected that the E-Learning information system will be able to answer existing challenges and problems. This study carried out a CATWOE analysis of the holons and elements (Client, Actor, Transformation, World View, Owner, Environment) found in case studies, building E-Learning models by applying the roles of humans, processes and technology as knowledge-forming elements, then analysis. holons based on the modeling of the resulting Knowledge. The analysis of E-Learning needs is answered by the need between the internal staff of teachers, employees, counseling and external students and parents to improve the quality of teaching and learning activities and student development.